1994
DOI: 10.3109/10715769409145637
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Tocopherol Depletion and Coenzyme Q During Lipid Peroxidation in rat Liver Mitochondria

Abstract: In order to evaluate different mitochondrial antioxidant systems, the depletion of alpha-tocopherol and the levels of the reduced and oxidized forms of CoQ were measured in rat liver mitochondria during Fe++/ascorbate and NADPH/ADP/Fe++ induced lipid peroxidation. During the induction phase of malondialdehyde formation, alpha-tocopherol declined moderately to about 80% of initial contents, whereas the total CoQ pool remained nearly unchanged, but reduced CoQ9 continuously declined. At the start of massive malo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…Coenzyme Q also serves as an important antioxidant in both mitochondria and lipid membranes (4,5). Coenzyme Q, which also is known as ubiquinone, is a lipid-soluble compound composed of a redox active quinoid moiety and a hydrophobic ''tail.''…”
mentioning
confidence: 99%
“…Coenzyme Q also serves as an important antioxidant in both mitochondria and lipid membranes (4,5). Coenzyme Q, which also is known as ubiquinone, is a lipid-soluble compound composed of a redox active quinoid moiety and a hydrophobic ''tail.''…”
mentioning
confidence: 99%
“…CoQ 10 was also found to be an important antioxidant, which protects cell and mitochondria membranes against oxidization and regenerates α-tocopherol (Noack et al, 1994;Nohl et al, 1999;Mukai et al, 1990). A number of preclinical and clinical reports on the antioxidant effect of CoQ 10 following oral supplementation were published, including reports on the prevention of LDL peroxidation (Mohr et al, 1992), administration to a patient with cardiovascular disease (Singh et al, 2003), hypertension (Rosenfeldt et al, 2007), angina pectoris (Singh et al, 1998), and neurodegenerative disorders (Parkinson's disease and Huntington's disease) (Young et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation of vitamin E prior to thioacetamide treatment prevented the toxicity induced by thioacetamide and lessened the reduction in values of all the mitochondrial parameters studied. The induction of lipid peroxidation in vitro in rat liver mitochondria by Fee /ascorbate and NADPH/ADP/Fe2+ caused an 80% decrease in a-tocopherol concentrations accompanied by an increase in lipid peroxide levels [34]. Thomas et al [35] showed that vitamin E deficiency led to reduced stability of mitochondrial membranes and decreased the rate of oxygen utilization with both NADH-and FADH2-linked substrates.…”
Section: Resultsmentioning
confidence: 99%